2018
DOI: 10.1159/000488491
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Retinal Vascular Density as a Screening Tool for Ageing and Stroke

Abstract: Objectives: To measure the density of retinal vessels from digitized fundus photographs in patients with recent stroke and age-matched controls. To investigate whether the parameter retinal vascular density (RVD) served as a quantitative marker for cerebrovascular events. Methods: Digitized fundus photographs of n = 158 subjects with stroke or transient ischemic attack within 1 year at the time of examination and n = 1,250 age-matched controls without any remarkable medical history were examined. Sex, hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Subjects recruited were local Chinese patients between the ages of 40 and 70 years who had been diagnosed with essential hypertension. Excluded from the study were participants with moderate or severe refractive error (higher than +3.0 diopter or lower than -3.0 diopter), history of glaucoma, history of ophthalmic surgery or retinal diseases, secondary causes of hypertension, BP higher than 160/100 after treatment, HbA1c higher than 6.1%, cardiac functional classification higher than grade 1, hypertensive complications other than retinopathy, coronary heart disease, 23 stroke history, 24 neurodegenerative diseases, 25 migraine, 26 or sleep apnea. 27 Patients with arrythmia or mental disorders or who were undergoing hormone therapies were also excluded for health and safety reasons.…”
Section: Methods Study Participantsmentioning
confidence: 99%
“…Subjects recruited were local Chinese patients between the ages of 40 and 70 years who had been diagnosed with essential hypertension. Excluded from the study were participants with moderate or severe refractive error (higher than +3.0 diopter or lower than -3.0 diopter), history of glaucoma, history of ophthalmic surgery or retinal diseases, secondary causes of hypertension, BP higher than 160/100 after treatment, HbA1c higher than 6.1%, cardiac functional classification higher than grade 1, hypertensive complications other than retinopathy, coronary heart disease, 23 stroke history, 24 neurodegenerative diseases, 25 migraine, 26 or sleep apnea. 27 Patients with arrythmia or mental disorders or who were undergoing hormone therapies were also excluded for health and safety reasons.…”
Section: Methods Study Participantsmentioning
confidence: 99%
“…Blood vessel density was evaluated as the ratio of vessel area to the area of the ROI without the OD (Sprödhuber et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we showed that RSSI patients have significantly reduced pRNFL thickness and have a larger FAZ area than the healthy controls. Previous reports used fundus photography to evaluate the retinal vasculature in ischemic stroke (9,14). Nonetheless, using these imaging modalities limits the resolution and depth of imaging; moreover, these imaging modalities cannot visualize the deeper retinal layers in the retina and cannot give additional information on the capillary structure in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports (7,9,21) used different algorithms to evaluate the photography in patients with ischemic stroke; these reports showed that patients with ischemic stroke have significant arteriolar and venular changes than healthy controls. Sprodhuber et al (9) also showed that patients with ischemic stroke have significantly reduced retinal vascular density than healthy controls. The SRCP is within the retinal nerve fiber layer (RNFL) and superficial portion of the ganglion cell complex (GCC), which consists of both large vessels and microvessels (22) as seen via the fundus photography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation